Profitability and technical efficiency of aquaculture in Punjab, India - Singh, D. R.; Vasisht, A. K.; Kumar, Shiv (Indian Journal of Fisheries, 2015)
The profitability and technical efficiency aspects of aquaculture in Punjab were examined using primary data pertaining to the year 2007-08 using cost and return concepts and stochastic frontier production function, respectively. Study showed that only two-fifth of the farms were using nursery ponds for fingerlings in early stages and few farmers were using branded feed. Application of chemical fertilisers and manures were directly and inversely related to farm size. Differences between observed and frontier output is attributed mainly to the inefficient use of resources which are under the control of fish farmers. Use of nursery, high proportion of rohu and training received by fish farmers were significantly affecting the technical efficiency. Aquaculture in Punjab is high yielding and profitable despite certain constraints. High cost of feed, low dissolved oxygen, poor availability of electricity, inadequate seed supply and poor quality of seed were perceived as the major constraints to aquaculture. The findings indicated that the farmers need to be trained for use of nursery ponds and optimum mix of resources to increase profitability in fish production. Further there is urgent need for development of low cost feed and establishment of more hatcheries to meet the demand of disease free and disease resistant fish/shrimp seed with strict quarantine measures.